INDIAN ECONOMY PERFORMANCE AND POLICIES - SINHA V C; SUDHA PANDEYA; SUDHIR KUMAR SINHA (AGRA SBPD PUBLICATIONS, 2025)
"Indian Economy" by Dr. V.C. Sinha is a comprehensive textbook designed for university students, focusing on the modern features, challenges, and structure of the Indian economy using a blend of theory, data, tables, and diagrams to present concepts in a simple and systematic way.
INDIAN ECONOMY
ECONOMICS
BBA & MBA
Keywords: ECONOMICS; MANAGEMENT